Dynamical Form-Factor of Neutron Scattering by DNA Solitons - Yakushevich, L.V. (Kluwer Academic Publishers, 1999)
Method of scattering of slow neutrons has been considered in recent years as a rather perspective way to study the nonlinear DNA dynamics. In this paper we present the results of theoretical calculations of the dynamical form-factor of the scattering. The calculations were made on the basis of the nonlinear mathematical model which takes into account rotational motions of bases around the sugar-phosphate chains. The results of the calculations are considered as predictions for further neutron scattering experiments.